India Vs Pakistan War, Triggering Nuclear War and Its Impact on The Indonesian Economy (International Forum of Researchers and Lecturers, 2025)
The war between India and Pakistan has had a devastating impact on the economies of both the countries directly involved and those indirectly affected. The economic impacts of this armed conflict include significant infrastructure damage, reduced production capacity, soaring inflation, rising unemployment, and reduced investment flows. This geopolitical instability has also fueled uncertainty in global financial markets, triggering a